Nanocomposites of PVA/cellulose nanocrystals: Comparative and stretch drawn properties. (4th September 2021) - Ejara, Tolessa Mengistu; Balakrishnan, Subramanian; Kim, Jeong Cheol
Abstract: Polyvinyl alcohol (PVA) nanocomposites were made using two different cellulose nanocrystals (CNCs). Sugarcane bagasse‐based CNC and a commercial CNC were used in preparing nanocomposites. Both types of nanocomposites were prepared by solution casting method at 5 wt% CNC. PVA and nanocomposites films were also stretch‐drawn four times to study the nature of reinforcement by two different CNCs. Fourier transform infrared spectroscopy was used to examine functional group characteristics. Nanocomposite morphology and crystalline structures were analyzed using a scanning electron microscope and X‐ray diffraction, respectively. Thermogravimetric analysis and differential scanning calorimetry were used to study thermal properties. Tensile properties were used to study mechanical properties. Commercial CNC reinforcement improves the tensile properties of PVA. However, laboratory CNC reinforcement decreases the tensile properties of PVA due to nanocrystal agglomeration and uneven dispersion. All stretch‐drawn nanocomposite films showed a significant increase in tensile strength and modulus values at the expense of strain at break. Water absorption of PVA/commercial CNC nanocomposites was slightly higher than that of pure PVA. Abstract : Tensile stress vs. strain curves of un‐drawn samples (a) neat PVA, (b) PVA/lab. CNC and (c) PVA/com. CNC. Tensile stress vs. strain curves of stretch‐drawn samples (a) neat PVA, (b) PVA/lab. CNC and (c) PVA/com. CNC.